Informal Peer Review at the heart of the Livestock and Climate Initiative's Occasional Feeds Conversations - Spinelli, Madison; Duncan, Alan J. (CGIAR System Organization, 2024)
Discussion on how informal peer review is at the center of the CGIARResearch Initiative on Livestock and Climate's Feed and Forage work.